2006
DOI: 10.1103/physrevb.74.134410
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistivity as a probe to the field-induced change of magnetic entropy inRAl2compounds(R=Pr,et al.

Abstract: The heat capacity C P ͑T͒ of the ferromagnetic compounds RAl 2 ͑R =Pr,Nd,Tb,Dy,Ho,Er͒ was measured at zero and applied magnetic field of 5 T in the temperature interval from 2 to 200 K. From these results are calculated the magnetic component of the entropy change, −⌬S mag ͑T͒ = S͑0,T͒ − S͑H , T͒. From resistivity measurements, ͑H , T͒, from 2 to 300 K in the same compounds, we calculated the resistivity change due to the applied magnetic field, −⌬ mag ͑T͒ = ͓ mag ͑0,T͒ − mag ͑H , T͔͒. The results are compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 21 publications
17
46
1
Order By: Relevance
“…If we choose R such that RAl 2 shows a ferromagnetic transition, interesting magnetic properties are expected to be observed in the pseudobinary system Ce 1−x R x Al 2 because of the competition between the ferromagnetic interaction of RAl 2 (x = 1) and the antiferromagnetic interaction of CeAl 2 (x = 0). In particular, ErAl 2 exhibits ferromagnetic ordering at approximately T C =13 K, 11) which is relatively close to the T N of CeAl 2 compared with the T C of the other RAl 2 compounds. Moreover, the easy axis of ErAl 2 is [111], 12,13) which is the same as that of CeAl 2 in the antiferromagnetic ground state.…”
Section: Introductionmentioning
confidence: 60%
“…If we choose R such that RAl 2 shows a ferromagnetic transition, interesting magnetic properties are expected to be observed in the pseudobinary system Ce 1−x R x Al 2 because of the competition between the ferromagnetic interaction of RAl 2 (x = 1) and the antiferromagnetic interaction of CeAl 2 (x = 0). In particular, ErAl 2 exhibits ferromagnetic ordering at approximately T C =13 K, 11) which is relatively close to the T N of CeAl 2 compared with the T C of the other RAl 2 compounds. Moreover, the easy axis of ErAl 2 is [111], 12,13) which is the same as that of CeAl 2 in the antiferromagnetic ground state.…”
Section: Introductionmentioning
confidence: 60%
“…where magnetic eld H 0 = 0 and H j max = H with j = 1, ..., j max while σ i and σ i+1 were the values of magnetization at temperature T i and T i+1 , respectively [8]. Magnetic entropy change vs temperature, for several external magnetic elds, is shown in Fig.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…They reported a satisfactory experimental correlation between ÀDS mag ¼ [S mag (0,T) À S mag (H,T)] and ÀDr mag ¼ [r mag (0,T) À r mag (H,T)] in the measured T-range along the [110] direction and above T C in the [100] direction. Such a correlation was first proposed by Campoy et al [1] for the RAl 2 polycrystalline series; they showed that DS mag $ T TC m ¼ F$Dr mag , where F is an adjust factor and m ¼ 1 for T < T C and m ¼ 0 for T > T C . This power-T-correction would be valid in the absence of elastic effects, negligible dependence of phonon spectra and Fermi energy, and carrier concentration with a magnetic field.…”
Section: Introductionmentioning
confidence: 88%
“…Also, one can relate some quantities with similar behavior to the evolution of the state of the system. For instance, the magnetoresistivity change (Dr mag ) of magnetic materials is of great interest, among other reasons, due to the possibility of connecting with the magnetic entropy change (DS mag ) [1]. In this respect, one subject of interest is to study the possibility of this connection in the presence of SR.…”
Section: Introductionmentioning
confidence: 99%